The Repressive Policy of the Soviet Totalitarian Authorities Towards the Evangelical Baptist Christians of Ukraine - Vysovenʹ, Oksana Ivanivna (Occasional papers on religion in Eastern Europe, 2023)
The punitive and repressive machine of the totalitarian regime worked to destroy politically hopeless citizens of the Union of Soviet Socialist Republics, and essentially religious people who made any sacrifices for the sake of their beliefs. A large part of them died in Stalin's concentration camps from diseases and malnutrition, as well as from difficult working conditions. Many prisoners were sentenced to be shot. Their families were harassed by law enforcement agencies, harassed in the press, at work. During the Khrushchev period, after the announcement of the anti-religious campaign and before the collapse of the Soviet Union, the children and grandchildren of former prisoners of conscience filled high-security prisons and penal colonies. The families of prisoners of conscience suffered from the persecution of law enforcement agencies, Party-Komsomol and school activists at large. Members of the Evangelical Baptist Christians fraternity were subjected to physical and moral torture by the punitive and repressive authorities both during pre-trial investigative actions and in exile camps and after serving their sentences. The cruelest conditions for believers were specially created in places of deprivation of liberty, in particular, they were not given timely first medical aid in case of illness or injury at work, which led to mutilation or even death. Despite the age, gender and health of prisoners of conscience, they were always used in the most difficult jobs. Convicted believers were also deprived of the following rights of prisoners: visits with relatives, early release for good behavior. The prison administration established additional punishments for keeping religious literature and reading prayers. After the release, most of the prisoners of conscience, despite the loss of health and the constant supervision of the police, the prosecutor's office and the local authorities, continued their spiritual service. Therefore, the fate of many faithful families of the Evangelical-Baptist brotherhood became for the citizens of Ukraine a symbol of the struggle for religious beliefs and inspired ordinary believers to oppose the atheistic policy of the communist regime. Almost 31 years after the collapse of the Soviet Union, the Putin regime began to actively use the methods of the punitive and repressive machine of the totalitarian system both in relation to its own population and in relation to the citizens of Ukraine, trying to finally solve the Ukrainian issue, namely: to finally liquidate the Ukrainian state and the Ukrainian nation.